Differential effects of genistein and 8-prenylgenistein on reproductive tissues in immature female mice - Xiao-Li Li (Taylor & Francis Group, 2019)
Context: We identified an active prenylated derivative of genistein, 8-prenylgenistein (8PG) from Erythrina variegata L. (Leguminosae) and found that 8PG increased osteoprotective effects of genistein in oestrogen-deficient mice. Objective: This study investigated and compared the oestrogenic effects of genistein and 8PG on uterus and vagina of immature mice. Materials and methods: Immature female CD-1 mice were orally treated with vehicle (Control, n = 10) or genistein (75 mg/kg, n = 10) or 8PG with low (8PG-L, 75 mg/kg, n = 10) and high dose (8PG-H, 150 mg/kg, n = 10) for 7 consecutive days by intragastric gavage. The uterus and vagina were harvested for histological and molecular measurements. Results: Treatment with genistein and 8PG-H significantly increased uterus index (1.98 ± 0.21 & 1.49 ± 0.16 mg/g) and vagina index (3.83 ± 0.11 & 3.13 ± 0.25 mg/g) as compared to untreated control (uterus, 1.12 ± 0.13 mg/g; vagina, 2.32 ± 0.18 mg/g). Accordingly, both genistein and 8PG-H made vaginal cells keratinized and induced uterine and vaginal hypertrophy associated with the endometrial proliferation. 8PG-L did not affect oestrus cycle and histology of uterus and vagina. Treatment of immature mice with genistein or 8PG-H upregulated protein expression of oestrogen receptor-α (ER-α) and proliferating cell nuclear antigen (PCNA), but 8PG-L did not alter ER-α and PCNA expression in uterus and vagina. Conclusion: This study indicated that 8-prenylgenistein exerted oestrogenic effects in immature female mice. The efficacy and safety of 8-prenylgenistein when applied in improving oestrogen deficiency-induced syndrome requires further elucidation.